Effective visualization of online terrain draped with satellite imageries - Ruzinoor, Che Mat; Abdul Rashid, Mohammed Shariff; Ahmad Rodzi, Mahmud (UTM, 2009)
The objective of this paper is to discuss on the effectiveness of visualizing online 3D terrain draped with different satellite imageries. The study area is at the Universiti Putra Malaysia, Serdang, Selangor, Malaysia. Topographic data of the study area is obtained from the contour maps of this area. High resolution satellite imageries of the same areas used in this project involved QUICKBIRD (0.6 meter resolution) and IKONOS (1 meter resolution). The R2V software is used for editing the contour data and Arc GIS used for overlaying the imageries over the 3D terrain data. Then the data is exporting into the Virtual Reality Markup Language for comparing the effectiveness of different satellite imageries. The effectiveness is compared based on the data size, imageries size, number of images tile, uploading time, frame per second and visualization quality. The results will suggest which satellite imageries is better for developing an effective online 3D terrain visualization utilizing GIS data.